Revisiting the thrifty gene hypothesis via 65 loci associated with susceptibility to type 2 diabetes. - Ayub, Q; Moutsianas, L; Chen, Y; Panoutsopoulou, K; Colonna, V; Pagani, L; Prokopenko, I; Ritchie, G; Tyler-Smith, C; McCarthy, M; Zeggini, E; Xue, Y (2014)
We have investigated the evidence for positive selection in samples of African, European, and East Asian ancestry at 65 loci associated with susceptibility to type 2 diabetes (T2D) previously identified through genome-wide association studies. Selection early in human evolutionary history is predicted to lead to ancestral risk alleles shared between populations, whereas late selection would result in population-specific signals at derived risk alleles. By using a wide variety of tests based on the site frequency spectrum, haplotype structure, and population differentiation, we found no global signal of enrichment for positive selection when we considered all T2D risk loci collectively. However, in a locus-by-locus analysis, we found nominal evidence for positive selection at 14 of the loci. Selection favored the protective and risk alleles in similar proportions, rather than the risk alleles specifically as predicted by the thrifty gene hypothesis, and may not be related to influence on diabetes. Overall, we conclude that past positive selection has not been a powerful influence driving the prevalence of T2D risk alleles.